2015
DOI: 10.1002/chir.22493
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Pidotimod Enantiomers With Chiralpak‐IA: Crystal Structure, Thermodynamic Parameters and Molecular Docking

Abstract: Pidotimod, a synthetic dipeptide, has two chiral centers with biological and immunological activity. Its enantiomers were characterized by x-ray crystallographic analysis. A chiral stationary phase (CSP) Chiralpak-IA based on amylose derivatized with tris-(3, 5-dimethylphenyl carbamate) was used to separate pidotimod enantiomers. The mobile phase was prepared in a ratio of 35:65:0.2 of methyl-tert-butyl-ether and acetonitrile trifluoroaceticacid. In addition, thermodynamics and molecular docking methods were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…Pidotimod oral liquid is a synthetic high-purity dipeptide. It is a common immunomodulator which can promote the specific and non-specific immune response and the phagocytosis, chemotaxis and killing effect of neutrophils and activate natural killer cell 13,14. Moreover, pidotimod can stimulate the activation of cellular immune process through promoting lymphocyte proliferation, effectively restoring the ratio of auxiliary T cells and inhibitory T cells and regulating the secretion of r-interferon and interleukin-2 15.…”
Section: Discussionmentioning
confidence: 99%
“…Pidotimod oral liquid is a synthetic high-purity dipeptide. It is a common immunomodulator which can promote the specific and non-specific immune response and the phagocytosis, chemotaxis and killing effect of neutrophils and activate natural killer cell 13,14. Moreover, pidotimod can stimulate the activation of cellular immune process through promoting lymphocyte proliferation, effectively restoring the ratio of auxiliary T cells and inhibitory T cells and regulating the secretion of r-interferon and interleukin-2 15.…”
Section: Discussionmentioning
confidence: 99%
“…In Table , a summary of some representative docking and MD studies published in the period 2015‐2018 is reported . Firstly, in polysaccharides modelling, an important issue concerns the preparation of a built polymer which is representative of the ‘real’ polysaccharide derivative.…”
Section: Polysaccharide Derivativesmentioning
confidence: 99%
“…In this regard, Shen and co‐workers performed a comparative docking by using ADMPC and cyclodextrins (CDs) as selectors and the enantiomers of pidotimod 13 as analytes. The difference of HBs, van der Waals, and internal torsional tension energy between the enantiomers and CSPs were found to be the leading causes of chiral recognition . Altomare and co‐workers modelled by docking the enantioseparation of three coumarin derivatives 14 on a 12‐mer ADMPC .…”
Section: Polysaccharide Derivativesmentioning
confidence: 99%
“…have also been determined, especially in commercial products or biological samples (pharmaceutical formulations, human urine, human or animal blood, human plasma, animal serum, etc.). Another heterogeneous group of analytes, including connectors for building metal-organic frameworks [116,117,124], intermediates for the synthesis of pharmaceuticals [111], natural and synthetic compounds [39,113,121,120], biological compounds [82,112,58,71,78,86,[61][62][63]77,75], natural alkaloids [121], biomolecules [115,54], organometallic compounds [119] and chiral metabolites [103,108,100,97,102,59,63,52] has been enantioseparated with these immobilized polysaccharides CSPs (see Table 2-4). Fig.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Several studies carried out on certain polysaccharide-based CSPs of immobilized type showed significant effects of acidic additive (or acidic with basic mixture additive) mainly on basic compounds [41,103,104,108,101,73,53,95,90,91,58,86,63,115,52] (see Tables 2-4).…”
Section: Accepted Manuscriptmentioning
confidence: 99%